Pelatihan Penyusunan Laporan Keuangan pada Perangkat Desa Kecamatan Bumijawa Kabupaten Tegal - Mirza Anindya Pangestika; Fatkhuri Fatkhuri (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
Village regulations are set out in Law No. 6/2014, which explains that a village has the authority to regulate and oversee the needs of the community, including the authority to manage their own finances. By law, the village government is required to report to the government on its performance as a result of this financial management authority. In its implementation, village financial management must be considered because it is very important. In the management of village finances, there are possible administrative and substantive risks that can lead to legal problems due to the less than optimal capacity of village officials in preparing reports and making reports on financial responsibilities. Seeing Permendagri Number 20 of 2018 regarding efforts to manage village finances starting from planning to accountability. This community service program is intended to provide training and knowledge for village officials in Bumijawa District on how to compile accountable, orderly, participatory, orderly, disciplined, and transparent financial reporting based on applicable regulations. In addition, this community service helps minimize the occurrence of financial irregularities in the future so that village financial managers can avoid things that are against policy